ANALISIS PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP KINERJA ESG PADA PERUSAHAAN PUBLIK DI INDONESIA - Murti, Karina; Wahyuni, Putri Dwi; Iskandar, Diah (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2026)
This study aims to analyze the influence of firm size and profitability on Environmental, Social, and Governance (ESG) performance of companies listed on the Indonesia Stock Exchange (IDX). The research sample consists of 40 companies indexed by Morningstar Sustainalytics and Thomson Reuters during the 2020–2024 period, resulting in 200 observations selected using purposive sampling. Secondary data were obtained from IDX publications, sustainability databases, and companies’ official reports. The data were analyzed using panel data regression with the Fixed Effect Model. The novelty of this study lies in the use of total sales as a proxy for firm size and the simultaneous examination of two profitability indicators, namely Return on Equity (ROE) and Net Profit Margin (NPM), to provide a more comprehensive explanation of ESG performance determinants in emerging market companies, particularly in Indonesia. Unlike previous studies that generally employ total assets as firm size measurement or focus on a single profitability indicator, this study integrates operational capacity and financial efficiency perspectives in explaining ESG performance. The results show that firm size has a positive and significant effect on ESG performance, indicating that larger companies tend to implement better sustainability practices due to greater resources and higher public pressure. Conversely, ROE has a negative and significant effect, suggesting that firms with higher shareholder returns tend to prioritize financial performance over sustainability initiatives. Meanwhile, NPM has no significant effect on ESG performance. In conclusion, ESG performance in Indonesian public companies is more strongly influenced by organizational scale than profitability efficiency. Future research is recommended to incorporate additional variables such as corporate governance characteristics, leverage, institutional ownership, or media exposure, and to extend the observation period.